Field evidence for a rapid adaptive plastic response in morphology and growth of littoral and pelagic brook charr: A reciprocal transplant experiment. (31st July 2017) - Pépino, Marc; Magnan, Pierre; Proulx, Raphaël
Abstract: Phenotypic plasticity, a process by which individuals modify their morphology, physiology, or behaviour in response to environmental changes, can be seen as the first step in adaptive evolution. Phenotypic plasticity is adaptive if two conditions are met: (1) the phenotype is associated with an environment (plastic response) and (2) the phenotype–environment association increases individual fitness (adaptive response). Using a reciprocal transplant experiment, we tested the hypothesis that functional morphological responses are correlated with growth at two organizational levels (between and within ecotypes) in brook charr. Four‐month‐old individuals from four littoral and four pelagic families raised in the laboratory were transferred into eight littoral (3 m × 4 m × 1.5 m depth) and eight pelagic (3 m × 4 m × 6 m depth) lake enclosures for a period of 12 weeks. Fin length (the main discriminant trait of the littoral and pelagic ecotypes) was less plastic than body shape. Growth was higher in the pelagic than in the littoral habitat, but offspring from littoral and pelagic parental origins did not experience higher growth in their respective habitats (comparison between ecotypes). The body shape of most individuals transplanted to their reciprocal environment shifted toward the form expected in that environment. This plastic response in body shape was functionally correlated with growth within ecotypes, but only in the littoral habitat. Furthermore, the within‐ecotype variance of both morphological traits and growth were higher in the littoral than in the pelagic habitat. Small phenotypic differences could have direct consequences on fitness in the less favourable habitat, inducing higher inter‐individual variance in growth and stronger phenotype–growth associations. We suggest that phenotypic accommodation and cryptic genetic variation, two mechanisms previously proposed as mechanisms involved in distinct situations, could be simultaneously involved to hasten the process of adaptive evolution in an unfavourable environment. A plain language summary is available for this article. Abstract : Plain Language Summary